2020
DOI: 10.3390/jmse8060414
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Wind Turbines and Fish Farms: An Evaluation of Potential Risks to Marine and Coastal Bird Species

Abstract: Expansion of marine aquaculture into more remote areas will likely accelerate over the next decade. Integrating Marine Renewable Energy (MRE) generation technologies (e.g., wind turbines) into remote, off-grid aquaculture sites will reduce reliance on fossil fuels by allowing localised low-carbon power generation, but may also result in novel environmental pressures. In this study, we undertook a thought experiment to assess the potential for increased collision risks to local marine and coastal bird species o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…This study suggested there was no negative impacts of operating wind turbines observed on the growth of these species. Although there have been concepts, models, protocols, and social-economic assessments on the co-location of OWF and mariculture for more sustainable usage of marine space [23][24][25][26][27][28], there is scant information about field research on the impacts of operating offshore wind turbines on mariculture. Even this study was conducted in natural sites with complex environmental factors, it still provides valuable information for future mariculture and OWF development.…”
Section: The Growths Of Tested Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…This study suggested there was no negative impacts of operating wind turbines observed on the growth of these species. Although there have been concepts, models, protocols, and social-economic assessments on the co-location of OWF and mariculture for more sustainable usage of marine space [23][24][25][26][27][28], there is scant information about field research on the impacts of operating offshore wind turbines on mariculture. Even this study was conducted in natural sites with complex environmental factors, it still provides valuable information for future mariculture and OWF development.…”
Section: The Growths Of Tested Speciesmentioning
confidence: 99%
“…Especially when the modern mariculture industry is, at least partially, moving or testing to move to more remoted offshore water using larger scale platforms, renewable energy sources from the sea (i.e., wind energy) might be a good source of energy to replace the diesel generators for electrical power [30]. The concept of a "Multipurpose Platform" integrating wind power and model offshore mariculture structure is being developed, although it may be at a very early stage [26]. This study provided first handed information for the risk assessment for potential environmental impacts of wind farm unites on selected important farming species [33,34].…”
Section: Co-existing Of Offshore Wind Farms and Mariculturementioning
confidence: 99%
“…ORE can impact species both indirectly, e.g., by changing habitat properties and directly, e.g., by causing collision risks with moving turbine components (Vanermen et al, 2019;Benjamins et al, 2020) and, for diving species, with static underwater structures (Grecian et al, 2010). ORE site selection is fundamentally important to minimize the direct and indirect impacts on selected species.…”
Section: Introductionmentioning
confidence: 99%
“…ORE site selection is fundamentally important to minimize the direct and indirect impacts on selected species. These impacts could be minimal (Benjamins et al, 2020) or severe when located in key areas, e.g., migration routes, feeding ground (Polaris Wind Power Network, 2018;Vanermen et al, 2019). A main concern, especially when many turbines are placed in close proximity, is the impact that ORE devices can have on acoustically-sensitive species by producing continuous low frequency noise (Madsen et al, 2006;Tougaard et al, 2009Tougaard et al, , 2020Bailey et al, 2010;Brandt et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Humans have caused increasingly severe ocean pollution as the economy of coastal areas develops and urbanization accelerates [1][2][3]. The land-based domestic and production sewage brought by the rivers flowing into the ocean has placed a considerable pressure on coastal waters, reducing their water quality, and it may even affect threatened bird habitats [4,5].…”
Section: Introductionmentioning
confidence: 99%